2019
DOI: 10.3329/kyamcj.v10i1.41481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prophylactic Effect of Intramuscular Diclofenac Sodium for Prevention of Succinylcholine-Induced Myalgia

Abstract: Background: Succinylcholine a depolarizing muscle relaxant with rapid onset, predictable course and short duration of action is associated with myalgia. Objectives: To assess the efficacy of intramuscular injection of diclofenac sodium in preventing succinylcholine-induced myalgia. Materials and Methods: Eighty healthy adults scheduled for elective surgery under general anesthesia were enrolledin a double-blind study and randomly allocated into two groups of forty patients. Patients in Group I (dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Patients who hadn’t taken premeditations like non-steroidal anti-inflammatory drugs (NSAIDs) were around seven times more likely to develop suxamethonium-induced postoperative myalgia (AOR 7.2; 95% CI 3.2–16.2). This is supported by studies that revealed, that patients premedicated with diclofenac had a significant reduction in the prevalence and intensity of myalgia 16 , 32 , 36 , 39 , 40 . Also, it is supported by another study that showed that pretreatment with oral aspirin and Ketorolac was effective in the reduction of suxamethonium-induced myalgia prevalence 40 , 45 .…”
Section: Discussionmentioning
confidence: 56%
“…Patients who hadn’t taken premeditations like non-steroidal anti-inflammatory drugs (NSAIDs) were around seven times more likely to develop suxamethonium-induced postoperative myalgia (AOR 7.2; 95% CI 3.2–16.2). This is supported by studies that revealed, that patients premedicated with diclofenac had a significant reduction in the prevalence and intensity of myalgia 16 , 32 , 36 , 39 , 40 . Also, it is supported by another study that showed that pretreatment with oral aspirin and Ketorolac was effective in the reduction of suxamethonium-induced myalgia prevalence 40 , 45 .…”
Section: Discussionmentioning
confidence: 56%
“…Another proposed mechanism is typically associated with increased levels of serum potassium and myoglobin, leading to enhanced creatine kinase and immediate postoperative muscle pain. [3][4][5] Postoperative myalgia is a prevalent adverse effect of succinylcholine, occurring in 41% to 92% of cases.…”
Section: Introductionmentioning
confidence: 99%